ANALISIS PERKEMBANGAN TEKNOLOGI M-BCA DAN KEAMANAN SIBER DI BANK CENTRAL ASIA - Rahmi Alfarizi; Achmad Justitio Satrio; Yendrikho Oktaviand Praseyto; Muhammad Firdaus Syahputra (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The implementation of M-BCA (Mobile Banking BCA) at Bank Central Asia (BCA) has significantly enhanced customer access to banking services and financial transactions. Governed by Articles 1 and 3 of Law No. 10 of 1998 on Banking, which emphasizes the necessity for technological innovation in banking services and customer protection during financial transactions, M-BCA aligns with these principles by offering transparent and efficient access through smartphones. Customers can conduct banking transactions anytime and anywhere without visiting physical branches, thereby improving transaction speed and efficiency.Additionally, M-BCA incorporates advanced security measures, including dual authentication mechanisms like Personal Identification Numbers (PINs) and One-Time Passwords (OTPs), which mitigate unauthorized access and reduce fraud risks. Compliance with relevant regulations, such as Bank Indonesia Regulation No. 18/40/PBI/2016 on electronic money services, further strengthens customer trust in BCA's electronic banking.Despite the positive impacts, challenges remain, particularly regarding telecommunications infrastructure in rural areas, which can hinder access to M-BCA services. Continuous investment in cybersecurity is essential to protect personal data from cyber threats. BCA's proactive strategies include enhancing security systems, employee training on cybersecurity practices, and maintaining compliance with data protection regulations. Overall, M-BCA has expanded financial inclusion while improving customer experiences in banking services, necessitating collaborative efforts to address existing challenges.